ISLAM DAN PRAKTIK PEMBERDAYAAN PEREMPUAN: STUDI TERHADAP IMPLEMENTASI NILAI-NILAI ISLAM DALAM PEMBERDAYAAN PEREMPUAN OLEH YAYASAN SAHABAT IBU DI YOGYAKARTA) - Widianto, Ahmad Arif (ASKETIK, 2017)
The emergence of non-governmental organizations (NGOs) were actively empowering women can supplement the lack of implementation of the programme of empowerment from the Government. In spite of all its shortcomings, a previous Study demonstrated that NGOs are more effective in carrying out the empowerment programs with a variety of models and strategies. Motherâs best friend Foundation (YSI) undertook to actively empower women in Yogyakarta and mengooptasi way to implement Islamic values not only in theoretical level but also practical. This paper discusses how YSI implement Islamic values and the implications for how the process of empowerment. This research uses qualitative approach method of verstehen to interpret the subjectâs understanding of research on Islamic-based empowerment. Data collection techniques using participatory observation and indepth interview against informants chosen by purposive. The results showed that the application of the values of Islam is more of an approach at once an instrument of womenâs empowerment. Islamic practices are applied in the empowerment of such a contract, pledge, pengajian, infaq is able to push the lancarnya the process of empowerment. The subject of research looked at that program of empowerment is the obligation to family and God. Nevertheless there are several members resigned because the program prove incriminating. On the one handthe implementation of Islamic values become the driving force of empowerment, on the other hand give rise to a difference of views among the participants and facilitator so that it becomes counterproductive. Keywords: NGOs, empowerment of women, the empowerment Strategy, values of Islam,